Grade Retention and Social Promotion Dichotomy: A Theoretical and Conceptual Analysis - Jeanette Jacobs; Oktavian Mantiri (Journal of Innovation in Educational and Cultural Research, 2022)
The dichotomy of retention versus promotion in education is persistent. It is a high stake decision teachers, administrators, and policymakers have to make. This article critically reviewed the die-hard retention factors and looked at alternative ways to deal with them. It emphasizes that the approach to repeating grades cannot be taken frivolously. Teachers, administrators, and policy makers' decisions will not only have life-long effects for the individuals upon whom they are placed, but they will undoubtedly affect the future societies as a whole. This article suggested that both teachers and administrators have the vital and deciding power to elect which approach to take, contextualizing curricula and professional development training sensitive to grade retention issues. Educational administrators and teachers must have the insight to recognize the failures and the courage to accept new ways to deal with old problems.